The first exome wide association study in Tunisia: identification of candidate loci and pathways with biological relevance for type 2 diabetes - Dallali, Hamza; Boukhalfa, Wided; Kheriji, Nadia; Fassatoui, Meriem; Jmel, Haifa; Hechmi, Meriem; Gouiza, Ismail; Gharbi, Mariem; Kammoun, Wafa; Mrad, Mehdi; Taoueb, Marouen; Krir, Asma; et al. (Frontiers in Endocrinology, 2023)
Introduction: Type 2 diabetes (T2D) is a multifactorial disease involving both genetic and environmental components. Several genome-wide association studies (GWAS) have been conducted to decipher potential genetic aberrations promoting the onset of this metabolic disorder. These GWAS have identified over 400 associated variants, mostly in the intronic or intergenic regions. Recently, a growing number of exome genotyping or exome sequencing experiments have identified coding variants associated with T2D. Such studies were mainly conducted in European populations, and the few candidate-gene replication studies in North African populations revealed inconsistent results. In the present study, we sought to discover the coding genetic etiology of T2D in the Tunisian population. Methods: We carried out a pilot Exome Wide Association Study (EWAS) on 50 Tunisian individuals. Single variant analysis was performed as implemented in PLINK on potentially deleterious coding variants. Subsequently, we applied gene-based and gene-set analyses using MAGMA software to identify genes and pathways associated with T2D. Potential signals were further replicated in an existing large in-silico dataset, involving up to 177116 European individuals. Results: Our analysis revealed, for the first time, promising associations between T2D and variations in MYORG gene, implicated in the skeletal muscle fiber development. Gene-set analysis identified two candidate pathways having nominal associations with T2D in our study samples, namely the positive regulation of neuron apoptotic process and the regulation of mucus secretion. These two pathways are implicated in the neurogenerative alterations and in the inflammatory mechanisms of metabolic diseases. In addition, replication analysis revealed nominal associations of the regulation of beta-cell development and the regulation of peptidase activity pathways with T2D, both in the Tunisian subjects and in the European in-silico dataset. Conclusions: The present study is the first EWAS to investigate the impact of single genetic variants and their aggregate effects on T2D risk in Africa. The disease markers, revealed by our pilot EWAS, will promote the understanding of the T2D pathophysiology in North Africa as well as the discovery of potential targets for T2D diagnosis and treatment.